Influence of the root canal filling technique on the success rate of primary endodontic treatments: a systematic review - Daniel Feijolo Marconi; Giovana Siocheta da Silva; Theodoro Weissheimer; Isadora Ames Silva; Gabriel Barcelos Só; Leonardo Thomasi Jahnke; Jovito Adiel Skupien; Marcus Vinicius Reis Só; Ricardo Abreu da Rosa (Restorative Dentistry & Endodontics)
ObjectivesThis study aimed to investigate the influence of different obturation techniques compared to cold lateral compaction on the success rate of primary non-surgical endodontic treatments.Materials and MethodsSystematic searches were performed for studies published up to May 17th, 2022 in MEDLINE/PubMed, Cochrane Library, Web of Science, Scopus, EMBASE, and Grey Literature Reports. Randomized clinical trials and nonrandomized (nonrandomized clinical trials, prospective or retrospective) studies that evaluated the success rate of primary non-surgical endodontic treatments obturated with the cold lateral compaction (control) and other obturation techniques were included. The revised Cochrane risk of bias tools for randomized trials (RoB 2) and nonrandomized studies of interventions (ROBINS-I) were used to evaluate the risk of bias. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) tool was used to evaluate the certainty of evidence.ResultsEleven studies (4 randomized clinical trials (RCTs), 4 prospective, and 3 retrospectives) were included. Two RCTs were classified as having some concerns risk of bias and 2 as a low risk of bias. Two nonrandomized studies were classified as having a critical risk of bias and 5 as having a moderate risk of bias. The GRADE analysis demonstrated a very low to moderate certainty of evidence.ConclusionsThis systematic review generally evidenced no differences in the success rate of primary non-surgical endodontic treatments when the cold lateral compaction technique and other obturation techniques are performed. Further well-designed studies are still necessary.